SISTEM INFORMASI PENJUALAN PADA UNIT TOKO KOPERASI PEGAWAI UBJ BERBASIS ANDROID - Dani Yusuf; Dwi Budi Srisulistiowati (Fakultas Ilmu Komputer dan Desain - Unsurya, 2019)
UBJ Employee Cooperative or commonly referred to as KP UBJ is an employee cooperative owned by University of Bhayangkara Jakarta Raya that serves savings and loan services and consumption cooperative shop units for its members. As for savings and loan activities because the funds managed are not so large and with the imposition of interest of only 5% per 10 months or 0.5 percent per month, the nominal benefits are not so large. Likewise with shop units, which for the time being have only served aqua gallons to work units at University of Bhayangkara Jakarta Raya with the current turnover, the benefits have not been too large, because of this KP UBJ has taken the initiative to develop business breakthrough, both on the business / capital capabilities of UBJ employee's own cooperatives by selling various kinds of Office Stationery or ATK and basic needs through an Android- based application by applying the Rapid Application Development (RAD) method and the application designed using the PHP and Java programming languages while for the database the application uses MySQL which can process store data, UBJ cooperative member data and user data and storage media in the database. With the sales application in the UBJ employee cooperative unit, it can simplify the buying and selling transaction process between UBJ's admin and cooperative members as well as the computerization of buying and selling transactions at UBJ Employee Cooperative Stores, making it easier for future data storage and search as well as a media campaign for store products. Â Keywords: Application, Sales, Cooperatives, Android